Food Consumption According to the Days of the Week - National Food Survey, 2008-2009 - Luana Silva Monteiro; Bruna Kulik Hassan; Camilla Chermont Prochnik Estima; Amanda de Moura Souza; Eliseu Verly Junior; Rosely Sichieri; Rosangela Alves Pereira (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE Evaluate the variations in energy, nutrients, and food groups intake between days of the week and weekend days in the Brazilian population. METHODS We used data from the first National Food Survey (2008-2009) of a one-day food log of a representative sample of the Brazilian population aged 10 years or older (n = 34,003). For the analyses, we considered the sample weights and the effect of the study design. The mean (and standard deviations) and frequencies (%) of energy, nutrients, and food groups consumption were estimated for weekdays (Monday to Friday) and weekend (Saturday and Sunday), we then estimated the differences according to the days of the week for the population strata analyzed. RESULTS The average daily energy intake for the weekend was 8% higher than the one observed for weekdays. The average percentage contribution of carbohydrate to the daily energy intake was higher during the week compared to Saturday and Sunday (56.3% versus 54.1%, p < 0.01). The inverse was observed for averages of the contribution to the daily intake of energy from total fat (26.8% versus 28.4%), saturated fat (9.1% versus 9.9%) and trans fat (1.4% versus 1.6%). The most significant changes between weekdays and weekend days were observed for eggs, sugar-added beverages, puff snacks and chips, beans, and pasta. During weekends, the frequency of beverage with added sugar consumption increased by 34%, the amount consumed increased by 42%, and the contribution to energy intake increased by 62% when compared to weekdays. CONCLUSIONS The Brazilian population increases energy intake and unhealthy food markers on weekends compared to weekdays.